2022
DOI: 10.4103/sjopt.sjopt_86_22
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial disease

Abstract: Rickettsioses are worldwide distributed infectious disease caused by intracellular small Gram-negative bacteria transmitted to humans by the bite of contaminated arthropods, such as ticks. Systemic disease typically consists of a triad of high fever, headache, and skin rash. It usually has a self-limited course, but severe, life-threatening complications can sometimes occur. It may be clinically difficult to differentiate rickettsial diseases from other febrile illnesses. Rickettsial infection has been largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Rickettsiae are able to invade and develop in a wide variety of host cells from different species and organs. In humans, the rickettsial pathogen is inoculated either by a tick or mite bite, or by scratching the skin after infected flea or louse excrement has been deposited on the skin [4] . They spread into the bloodstream, proliferating, and damaging the endothelium of small arteries, veins and capillaries and, in some cases, vascular smooth muscle cells, causing damage to the microcirculation of virtually every organ [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rickettsiae are able to invade and develop in a wide variety of host cells from different species and organs. In humans, the rickettsial pathogen is inoculated either by a tick or mite bite, or by scratching the skin after infected flea or louse excrement has been deposited on the skin [4] . They spread into the bloodstream, proliferating, and damaging the endothelium of small arteries, veins and capillaries and, in some cases, vascular smooth muscle cells, causing damage to the microcirculation of virtually every organ [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of rickettsial vasculitis consists of 100 mg doxycycline every 12 hours for at least 7 days, and for at least 2 days after apyrexia. Doxycycline is the drug of choice for rickettsial infections, and treatment should be started as soon as the diagnosis is suspected; indeed, the mortality rate is significantly lower in patients treated within the first 5 days of illness than in those treated later [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the visual field examination did not detect the visual field defect, but six months later, there was a definite sickle-shaped inferior visual defect that corresponded with the nerve fiber bundle defect (Figure 4b ). A study reported retinal nerve fiber bundle defect and focal retinal thinning on OCT but did not report a corresponding visual field defect [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visual recovery occurs over three to five months with a resolution of retinal lesions. Most studies and case reports reported good visual recovery in patients with PFR due to rickettsial disease [ 2 , 4 , 10 , 11 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another particularity in the case of our patient were the ophthalmologic complications which occurred only secondarily. Ocular involvement with retinitis and retinal vasculitis are common findings in RMFS patients, however they usually occur with the initial symptoms and respond well to therapy [ 11 ]. Pathophysiologically, ocular damage may be due to two mechanisms: on the one hand, a direct invasion of the retinal vessels by the bacteria and, on the other hand, as a secondary immunological response to the bacterium [ 12 ].…”
mentioning
confidence: 99%